Use of Preoperative MRI to Predict Vestibular Schwannoma Intraoperative Consistency and Facial Nerve Outcome - Copeland, William R.; Hoover, Jason M.; Morris, Jonathan M.; Driscoll, Colin L. W.; Link, Michael J. (Journal of Neurological Surgery Part B: Skull Base, 2013)
Objectives We sought to identify if preoperative schwannoma magnetic resonance imaging (MRI) intensities might predict intraoperative consistency. We then determined whether consistency correlated with facial nerve outcomes.Design Operative reports from 2000 to 2010 were searched for tumor description as either soft and/or suckable or firm and/or fibrous. Preoperative T1 and T2 sequences were then reviewed to identify intensities relative to gray matter. Facial nerve function was recorded at the time of most recent follow-up.Results Forty-six patients were included. No tumors were T1 hyperintense. Soft and firm schwannomas were equally likely to be T1 hypointense. On T2 sequences, however, soft schwannomas were more likely to be hyperintense (88% versus 14%, p < 0.005) whereas firm schwannomas were more likely to be hypointense (86% versus 6%, p < 0.005). There was a tendency for firm schwannomas to have worse facial nerve outcomes (43% versus 19%, p = 0.14).Conclusions Prediction of vestibular schwannoma intraoperative consistency based on T2 intensity seems promising. Furthermore, though not statistically significant, in this small pilot study firm schwannomas tended to have worse facial nerve outcomes. This potential ability to predict consistency and its correlation with facial nerve outcome may assist the surgeon in preoperative planning and patient counseling, though further data needs to be accumulated.
Keywords: vestibular schwannoma; acoustic neuroma; facial nerve outcome; tumor consistency; magnetic resonance imaging